Источники электромагнитной эмиссии в бетонах; Письма в Журнал технической физики; Т. 20, № 21 - Фурса Т. В. Татьяна Викторовна; Гордеев В. Ф.; Ласуков В. В. Владимир Васильевич; Малышков Ю. П. (1994, 1994)
Заглавие с экрана